2004
DOI: 10.1159/000081797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Congenital Heart Disease on Renal Function in Childhood

Abstract: Background: Nephropathy is a well-known complication of congenital heart disease (CHD), and the risk of developing renal impairment is particularly high in patients with cyanotic CHD. Most investigations of renal impairment in CHD have involved patients 20 years and older. This study investigated renal tubule function in pediatric patients with CHD, and compared findings in cyanotic and acyanotic groups. Methods: Twenty children with acyanotic CHD, 23 children with cyanotic CHD, and 13 healthy children were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…45 Cyanotic patients with CHD have unique risk factors for developing CKD. These include direct hypoxia leading to early renal tubular injury 46,47 and reactive erythrocytosis. This erythrocytosis induces secondary hyperviscosity leading to engorgement of the glomerular capillary beds, which in turn increases the efferent glomerular arteriolar resistance.…”
Section: Overviewmentioning
confidence: 99%
“…45 Cyanotic patients with CHD have unique risk factors for developing CKD. These include direct hypoxia leading to early renal tubular injury 46,47 and reactive erythrocytosis. This erythrocytosis induces secondary hyperviscosity leading to engorgement of the glomerular capillary beds, which in turn increases the efferent glomerular arteriolar resistance.…”
Section: Overviewmentioning
confidence: 99%
“…However, only a small number of clinical studies have been conducted with the aim of clarifying this hypothesis [6,7]. Tubular injury as well as glomerular injury have also been reported [8]. One of the aims of the present study, therefore, was to retrospectively analyze clinical and laboratory findings in order to clarify the risk factors and the mechanisms of the development and progression of CN.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that congestive heart failure patients were complicated with glomerular injury as indicated by increased albuminuria and decreased GFR. Therefore, the urinary microalbumin (mALB) level has been used to evaluate the glomerular functions (Agras et al 2005).…”
Section: Introductionmentioning
confidence: 99%